Cadaveric Skin Grafts May Greatly Increase the Healing Rate of Recalcitrant Ulcers When Used Both Alone and in Combination With Split-Thickness Skin Grafts. Issue 2 (February 2020) - Mosti, Giovanni; Mattaliano, Vincenzo; Magliaro, Antonio; Picerni, Pietro; Bastiani, Luca
Abstract : BACKGROUND: Leg ulcers that do not heal despite appropriate treatment are defined as recalcitrant ulcers. Large surface area, depth, and long duration represent some of most important factors impeding ulcer healing. After sharp debridement, dermal substitutes including skin from cadaver donors may increase the healing rate of recalcitrant ulcers reducing the risk of scar formation and recurrence. OBJECTIVE: Assessing if, after sharp debridement, dermal substitutes including skin from cadaver donors may increase the healing rate of recalcitrant ulcers reducing the risk of scar formation and recurrence. PATIENTS AND METHODS: Among patients admitted to our hospital for all types of chronic leg ulcers, we retrospectively reviewed the records of patients affected by recalcitrant ulcers (surface greater than 100 cm 2, tissue loss involving epidermis, dermis, and subcutaneous tissue, duration longer than 1 year, and showing no healing tendency). After sharp debridement, the ulcers were covered by allografts with strict follow-up after discharge. Multiple allografts were performed when necessary, and a final autograft was applied in case of incomplete healing. RESULTS: The records of 414 patients were analyzed. Forty-three patients were lost at follow-up, and the remaining 371 healed after 765 grafting procedures. In 163 patients, the ulcers healed by means of a final autograft. In all the remaining cases, allograft led to ulcer healing. CONCLUSION: Allografts represent an effective treatment option in case of recalcitrant, large, deep and long-lasting leg ulcers.